Special composite modified rubber for automobile cover tyre and preparation method of special composite modified rubber

Through the use of rubber materials with specific ratios and modified nanoparticles, combined with compounding and vulcanization processes, the problems of automotive tire rubber in aging, tear resistance and waterproof and slip resistance are solved, and high-performance automotive tire materials are achieved .

CN119463316AActive Publication Date: 2025-02-18SUNTOP TIRE WUXI CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411649872.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing composite modified rubber for automotive tires is aging and wearable in ultraviolet rays and air oxidation environments, has insufficient tear resistance, and has poor waterproof and anti-slip performance in harsh environments, which affects service life and safety.

Method used

Using natural rubber, composite rubber, aminosilane coupling agent, carbon material, modified nanoparticles, plasticizer, activator, dispersant, antioxidant, vulcanizing agent and vulcanizing accelerator with specific ratios, through the compounding and The vulcanization process forms a composite modified rubber with excellent wear resistance, aging resistance, temperature resistance and stability, waterproof and anti-slip properties.

Benefits of technology

It significantly improves the wear resistance, aging resistance, temperature stability, water resistance and slip resistance of rubber, extends the service life of the tire, enhances safety and comfort, and meets the high-performance requirements of modern automobile tires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140627810000151
    Figure BDA0005140627810000151
  • Figure BDA0005140627810000161
    Figure BDA0005140627810000161
Patent Text Reader

Abstract

The invention relates to the field of rubber materials, in particular to special composite modified rubber for an automobile cover tyre and a preparation method thereof. The special composite modified rubber for the automobile cover tyre is prepared from the following raw materials in parts by mass: 50-70 parts of natural rubber, 30-40 parts of composite rubber, 3-5 parts of an amino silane coupling agent, 30-50 parts of a carbon material, 15-25 parts of modified nanoparticles, 8-14 parts of a plasticizer, 3-5 parts of an activating agent, 2-4 parts of a dispersing agent, 1-1.5 parts of an antioxidant, 1-3 parts of a vulcanizing agent and 1-2 parts of a vulcanization accelerator. The prepared composite modified rubber special for the automobile cover tire has excellent wear resistance, can also keep good aging resistance, temperature-resistant stability, water resistance, skid resistance and the like, can effectively meet the performance requirements of the existing automobile field on automobile cover tire materials, and has very excellent market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of rubber materials, and in particular to a composite modified rubber specially used for automobile outer tires and a preparation method thereof. Background Art

[0002] With the development of the automobile industry, automobile tires, as an important part of vehicles, have a direct impact on the safety and comfort of the car. Therefore, the development of high-performance automobile tire materials has always been the focus of research. The composite modified rubber for automobile tires is designed to improve the wear resistance, waterproofness, aging resistance, heat stability and tear resistance of rubber by adding various functional fillers and modifiers to meet the high performance requirements of modern automobile tires.

[0003] Traditional automobile tire rubber mainly uses natural rubber (NR) and is supplemented with reinforcing agents such as carbon black and white carbon black to improve performance. However, with the increase in vehicle speed and the diversification of road conditions, traditional rubber materials can no longer fully meet the requirements in some performance aspects. Therefore, researchers began to explore new modification technologies and materials to further improve the comprehensive performance of rubber.

[0004] Although the existing composite modified rubber for automobile outer tires has improved the performance of tires to a certain extent, there are still the following problems. First, because the tires are exposed to ultraviolet light and air oxidation environments for a long time, they are prone to aging and wear, which greatly affects the service life of the tires; secondly, during driving, the tires may be punctured by sharp objects, and the existing composite modified rubbers still need to be improved in terms of tear resistance; finally, in some harsh environments in my country, the waterproof and anti-skid properties of the existing composite modified rubber for outer tires are poor, which limits its use quality in specific environments. Therefore, in order to effectively solve the above problems, the present application provides a composite modified rubber for automobile outer tires and a preparation method thereof. The composite modified rubber for automobile outer tires prepared by the present application not only has excellent wear resistance, but also can maintain good aging resistance, temperature stability, waterproof and anti-skid properties, etc., which can effectively meet the performance requirements of the existing automobile field for automobile outer tire materials and has a very excellent market prospect. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides a composite modified rubber for automobile tires. The raw materials are, by mass: 50 to 70 parts of natural rubber, 30 to 40 parts of composite rubber, 3 to 5 parts of aminosilane coupling agent, 30 to 50 parts of carbon material, 15 to 25 parts of modified nanoparticles, 8 to 14 parts of plasticizer, 3 to 5 parts of activator, 2 to 4 parts of dispersant, 1 to 1.5 parts of antioxidant, 1 to 3 parts of vulcanizer, and 1 to 2 parts of vulcanization accelerator.

[0006] As a preferred solution, the mass ratio of the natural rubber, the composite rubber and the carbon material is (55-65):(32-38):(35-42).

[0007] As a preferred solution, the mass ratio of the natural rubber, the composite rubber and the carbon material is (58-64): (34-36): (36-40).

[0008] As a preferred solution, the mass ratio of the natural rubber, the modified nanoparticles and the dispersant is (55-65): (18-24): (2.5-3.5).

[0009] As a preferred solution, the mass ratio of the natural rubber, the modified nanoparticles and the dispersant is (58-64): (20-23): (2.5-3).

[0010] As a preferred solution, the Mooney viscosity of the natural rubber is 85-100, and the condition is ML1+4@100°C.

[0011] As a preferred solution, the composite rubber is a composition of styrene-butadiene rubber and liquid nitrile rubber.

[0012] As a preferred solution, the mass ratio of the styrene-butadiene rubber to the liquid nitrile rubber is (3-4):(1.5-2).

[0013] As a preferred solution, the mass ratio of the styrene-butadiene rubber to the liquid nitrile rubber is (3.5-3.8):(1.6-1.8).

[0014] As a preferred solution, the kinematic viscosity of the liquid nitrile rubber is 11000-16000 cps, condition: 45°C.

[0015] As a preferred solution, the kinematic viscosity of the liquid nitrile rubber is 12000-14000 cps, condition: 45°C.

[0016] As a preferred solution, the Mooney viscosity of the styrene-butadiene rubber is 40-60, under the condition of ML1+4@100°C.

[0017] As a preferred solution, the Mooney viscosity of the styrene-butadiene rubber is 50-55, and the condition is ML1+4@100°C.

[0018] In this application, by adding the above-mentioned specific composite rubber compound and natural rubber compound, it is possible to ensure the wear resistance of the composite modified rubber while providing excellent aging resistance, temperature stability and waterproof and anti-skid performance. The compounding of the composite rubber compound with the above-mentioned specific viscosity can greatly enhance the wetting effect of the liquid rubber in the system in the mixture, and the modified nanoparticles added in this application can greatly enhance its dispersion stability in the composite rubber compound, avoiding the segregation and migration of the modified nanoparticles in the rubber system, thereby prompting it to stably provide mechanical connection, waterproof and wear-resistant sites; on the other hand, the added composite rubber compound can greatly improve the fluidity of the previous rubber compound, and the appropriate molecular chain length can be used as the connecting molecular chain of the composite rubber compound, while increasing the tightness of the internal colloid and increasing the movement resistance of water molecules and active groups, and increasing the connection movement rate of electrostatic particles and other charges, so that it can achieve rapid electron conduction dissipation in long-term ultraviolet light, outdoor and air oxidation environments, and achieve a high absorption conversion of ultraviolet light on the rubber compound surface, thereby obtaining excellent aging resistance and heat stability and other properties.

[0019] As a preferred solution, the aminosilane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0020] As a preferred solution, the aminosilane coupling agent is 3-aminopropyltriethoxysilane.

[0021] As a preferred solution, the carbon material is at least one of carbon black, carbon powder, graphene, graphene oxide and graphite.

[0022] As a preferred solution, the carbon material is carbon black.

[0023] As a preferred solution, the average particle size of the carbon black is 30 to 50 nm.

[0024] As a preferred solution, the preparation method of the modified nanoparticles comprises the following specific steps: S1: titanium dioxide and ammonia water are mixed and added to deionized water, the temperature is raised to 60-65°C, and a deionized water solution of ethyl orthosilicate, triethanolamine and γ-aminopropyltrimethoxysilane is added dropwise at a speed of 60-80 rpm for 0.8-1 h. After the addition is completed, the temperature is kept for reaction for 1.2-1.5 h. After completion, the pre-treated particles are centrifuged, filtered and dried to obtain pre-treated particles; S2: the pre-treated particles and anhydrous aluminum chloride are mixed and added to a DMF solution, the temperature is raised to 60-80 ℃ preheat for 1-2h, then raise the temperature to 100-110℃ and simultaneously add dropwise DMF solutions containing 1,4-benzenedicarboxylic acid and 1,4-benzenedicarboxylic acid-NH2 for 2-3h; S3: after the dropwise addition is completed, raise the temperature to 125-135℃, keep the temperature under reflux for 16-18h, naturally cool to room temperature after the reaction is completed, collect the solid product by filtration, and wash it with DMF several times to remove unreacted raw materials and other impurities, place the filtered product in a vacuum drying oven at 80-90℃ and dry overnight to remove residual solvent, and the product is obtained after completion.

[0025] As a preferred solution, the mass ratio of titanium dioxide, tetraethyl orthosilicate, triethanolamine and γ-aminopropyltrimethoxysilane is (3-3.5): (0.3-0.5): (0.05-0.08): (0.1-0.12).

[0026] As a preferred solution, the mass ratio of the pretreated particles, anhydrous aluminum chloride, 1,4-phthalic acid and 1,4-phthalic acid-NH2 is (1-1.5): (2-2.2): (1-1.2): (0.8-1).

[0027] As a preferred solution, the average particle size of the titanium dioxide is 10 to 20 nm.

[0028] As a preferred solution, the average particle size of the modified nanoparticles is 400-480 nm.

[0029] In this application, the addition of the modified nanoparticles can effectively improve the wear resistance, aging resistance, temperature stability and waterproof and anti-skid performance of the composite modified rubber. The modified nanoparticles can form a composite particle structure with titanium dioxide as the surface coating and framework particles as the main body. The existence of this structure can not only form a stable heterojunction electron flow structure, but also its unique structure can ensure the degree of exposure of the main framework particles to the outside, thereby ensuring excellent ultraviolet light absorption potential while avoiding the influence of the surface hydroxyl group of titanium dioxide on the waterproof and hygroscopic resistance of the particles, thereby greatly improving the ultraviolet and oxygen oxidation resistance by improving the electron hole recovery resistance under long-term ultraviolet light and air oxidation environment, thereby obtaining excellent aging resistance and temperature stability, and the surface fine particle surface formed by the modified nanoparticles can provide excellent wear resistance and anti-skid performance at the same time, and the rough peak-valley structure on the surface can block water molecules on the surface to form a continuous hydration layer, thereby obtaining excellent surface waterproof resistance.

[0030] As a preferred solution, the plasticizer is at least one of aromatic oil, paraffin oil, naphthenic oil, white oil and silicone oil.

[0031] As a preferred solution, the plasticizer is white oil.

[0032] As a preferred solution, the activator is at least one of magnesium oxide, calcium oxide, barium oxide and aluminum oxide.

[0033] As a preferred solution, the activator is magnesium oxide.

[0034] As a preferred solution, the average particle size of the activator is 0.5-1.5 μm.

[0035] As a preferred solution, the dispersant is at least one of zinc stearate, calcium stearate, tributyl phosphate, triphenyl phosphate and lauryl alcohol polyoxyethylene ether.

[0036] As a preferred solution, the dispersant is zinc stearate.

[0037] As a preferred solution, the antioxidant is at least one of BHT, antioxidant 1010, antioxidant 1076, antioxidant 1135 and antioxidant 245.

[0038] As a preferred solution, the antioxidant is antioxidant 1010 or antioxidant 1076.

[0039] As a preferred solution, the vulcanizing agent is sulfur.

[0040] As a preferred solution, the vulcanization accelerator is a combination of MBTS and DTDM.

[0041] As a preferred solution, the mass ratio of MBTS to DTDM is (3-3.5): (1.5-2).

[0042] The second aspect of the present application provides a method for preparing the above-mentioned composite modified rubber for automobile outer tires, which specifically includes the following steps: S1: putting natural rubber and composite rubber into an internal mixer, mixing and preheating at 90-95°C for 10-15 minutes, then adding aminosilane coupling agent, carbon material, modified nanoparticles and dispersant and mixing for 6-8 minutes, and continuing to add plasticizer, activator and antioxidant and mixing for 8-10 minutes; S2: adding vulcanizer and vulcanization accelerator and mixing for 5-7 minutes, after ensuring that all components are evenly dispersed, taking out the mixed rubber, cooling to room temperature, and extruding the cooled rubber into shape with an extruder; S3: putting the molded rubber into a vulcanizing tank, setting the vulcanization temperature to 130-145°C, the vulcanization pressure to 1.2-1.6MPa, and the vulcanization time to 30-35min. After the vulcanization is completed, taking out the rubber and naturally cooling it to room temperature to obtain the product.

[0043] The beneficial effects of this application are:

[0044] 1. The composite modified rubber for automobile outer tires provided in the present application not only has excellent wear resistance, but also has good aging resistance, temperature stability, waterproofness and anti-slip properties. It can effectively meet the performance requirements of automobile outer tire materials in the existing automobile field and has a very excellent market prospect.

[0045] 2. The composite modified rubber for automobile outer tires provided in the present application can provide excellent aging resistance, temperature stability and waterproof and anti-skid properties while ensuring the wear resistance of the composite modified rubber by adding specific composite rubber compounds and natural rubber compounding; the compounding of composite compounds with specific viscosity can greatly enhance the wetting effect of liquid rubber in the system in the mixture, and the modified nanoparticles added in the present application can greatly enhance its dispersion stability in the composite compounds, avoiding the segregation and migration of modified nanoparticles in the rubber system, thereby enabling it to stably provide mechanical connection, waterproof and wear-resistant sites.

[0046] 3. The present application provides a composite modified rubber for automobile outer tires. The added compound rubber can greatly improve the fluidity of the previous rubber. The suitable molecular chain length can serve as the connecting molecular chain of the composite rubber, increase the compactness of the internal colloid and improve the movement resistance of water molecules and active groups. At the same time, it increases the connection movement rate of electrostatic particles and other charges, thereby achieving rapid electron conduction dissipation in long-term ultraviolet light, outdoor and air oxidation environments, and achieving a high absorption and conversion of ultraviolet light on the surface of the rubber, thereby obtaining excellent aging resistance and heat stability and other properties.

[0047] 4. The present application provides a composite modified rubber for automobile outer tires, wherein the modified nanoparticles added thereto can form a composite particle structure with titanium dioxide as the surface coating and framework particles as the main body. The existence of this structure can not only form a stable heterojunction electron flow structure, but its unique structure can also ensure the degree of exposure of the main framework particles to the outside, thereby ensuring excellent ultraviolet light absorption potential while avoiding the influence of the surface hydroxyl groups of titanium dioxide on the waterproof and hygroscopic properties of the particles. Therefore, under long-term ultraviolet light and air oxidation environments, the resistance to electron-hole recovery can be improved, thereby greatly improving the resistance to ultraviolet and oxygen oxidation, thereby obtaining excellent aging resistance and temperature resistance stability. The surface fine particles formed by the modified nanoparticles can provide excellent wear resistance and anti-slip properties at the same time, and the rough peak-valley structure on the surface can block water molecules on the surface to form a continuous hydration layer, thereby obtaining excellent surface waterproof resistance. DETAILED DESCRIPTION

[0048] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0049] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0050] Example 1

[0051] Example 1 The first aspect provides a composite modified rubber for automobile tires. The raw materials, in parts by mass, are: 61.6 parts of natural rubber, 34.5 parts of composite rubber, 3.8 parts of aminosilane coupling agent, 38.8 parts of carbon material, 22.5 parts of modified nanoparticles, 9.8 parts of plasticizer, 3.4 parts of activator, 2.8 parts of dispersant, 1.2 parts of antioxidant, 2.1 parts of vulcanizer, and 1.6 parts of vulcanization accelerator.

[0052] The Mooney viscosity of the natural rubber was 88, under the condition of ML1+4@100°C, and the product was purchased from the RSS-3 model sold by the Thai Natural Rubber Public Company.

[0053] The composite rubber is a composition of styrene-butadiene rubber and liquid nitrile rubber, and the mass ratio of the two is 3.6:1.6.

[0054] The Mooney viscosity of styrene butadiene rubber is 52, condition: ML1+4@100°C, and the SBR1500 model product was purchased from Jilin Petrochemical.

[0055] The kinematic viscosity of the liquid nitrile rubber is 12500 cps, condition: 45°C, and it is purchased from NBR series products of corresponding viscosity sold by Shandong Shengrui Chemical Technology Co., Ltd.

[0056] The aminosilane coupling agent is 3-aminopropyltriethoxysilane; the carbon material is carbon black N330, and the average particle size is 30 nm.

[0057] The preparation method of the modified nanoparticles comprises the following specific steps: S1: 3.3 parts of titanium dioxide and 0.2 parts of ammonia water are mixed and added to 100 parts of deionized water, the temperature is raised to 65° C., and 60 parts of a deionized water solution of 0.45 parts of ethyl orthosilicate, 0.06 parts of triethanolamine and 0.11 parts of γ-aminopropyltrimethoxysilane are added dropwise at a speed of 80 rpm, the dropping time is 1 hour, and after the dropping is completed, the temperature is kept for reaction for 1.2 hours, and after the completion, the pre-treated particles are centrifuged, filtered and dried to obtain pre-treated particles; S2: 1.2 parts of the pre-treated particles and 2.1 parts of anhydrous aluminum chloride are mixed and added to 120 parts of DM F solution, heat to 75℃ and preheat for 2h, then heat to 105℃ and simultaneously add 40 parts of DMF solution containing 1.1 parts of 1,4-phthalic acid and 0.9 parts of 1,4-phthalic acid-NH2 dropwise, and the addition time is 2h; S3: after the addition is completed, heat to 125℃, keep reflux reaction for 18h, and naturally cool to room temperature after the reaction is completed. Collect the solid product by filtration, and wash it with DMF several times to remove unreacted raw materials and other impurities. Dry the filtered product in a vacuum drying oven at 85℃ overnight to remove residual solvent, and obtain the product after completion.

[0058] The average particle size of titanium dioxide is 12 nm; the average particle size of the obtained modified nanoparticles is 424 nm.

[0059] The plasticizer is white oil #5; the activator is magnesium oxide with an average particle size of 0.8 μm; the dispersant is zinc stearate; and the antioxidant is antioxidant 1010.

[0060] The vulcanizing agent is sulfur; the vulcanization accelerator is a composition of MBTS and DTDM, and the mass ratio of the two is 3.2:1.6.

[0061] The second aspect of the present embodiment provides a method for preparing the above-mentioned composite modified rubber for automobile outer tires, which specifically includes the following steps: S1: putting natural rubber and composite rubber into an internal mixer, mixing and preheating at 92°C for 12 minutes, then adding aminosilane coupling agent, carbon material, modified nanoparticles and dispersant and mixing for 6.5 minutes, and continuing to add plasticizer, activator and antioxidant and mixing for 8.5 minutes; S2: adding vulcanizer and vulcanization accelerator and mixing for 6 minutes, after ensuring that all components are evenly dispersed, taking out the mixed rubber, cooling to room temperature, and extruding the cooled rubber into shape with an extruder; S3: putting the molded rubber into a vulcanizing tank, setting the vulcanization temperature to 135°C, the vulcanization pressure to 1.5MPa, and the vulcanization time to 32 minutes. After the vulcanization is completed, taking out the rubber and naturally cooling it to room temperature.

[0062] Example 2

[0063] The specific implementation of this embodiment is basically the same as that of Example 1, except that: the composite modified rubber for automobile outer tires, in parts by mass, the raw materials are: 55.2 parts of natural rubber, 38 parts of composite rubber, 3.8 parts of aminosilane coupling agent, 35.5 parts of carbon material, 18.8 parts of modified nanoparticles, 9.8 parts of plasticizer, 3.4 parts of activator, 2.5 parts of dispersant, 1.2 parts of antioxidant, 2.1 parts of vulcanizing agent, and 1.6 parts of vulcanization accelerator.

[0064] The composite rubber is a composition of styrene-butadiene rubber and liquid nitrile rubber, and the mass ratio of the two is 3:2.

[0065] The vulcanization accelerator is a composition of MBTS and DTDM, and the mass ratio of the two is 3.5:1.5.

[0066] Example 3

[0067] The specific implementation of this embodiment is basically the same as that of Example 1, except that: the composite modified rubber for automobile outer tires, in parts by mass, the raw materials are: 64.8 parts of natural rubber, 32.5 parts of composite rubber, 3.8 parts of aminosilane coupling agent, 41.5 parts of carbon material, 24 parts of modified nanoparticles, 9.8 parts of plasticizer, 3.4 parts of activator, 3.5 parts of dispersant, 1.2 parts of antioxidant, 2.1 parts of vulcanizing agent, and 1.6 parts of vulcanization accelerator.

[0068] The composite rubber is a composition of styrene-butadiene rubber and liquid nitrile rubber, and the mass ratio of the two is 4:1.5.

[0069] The vulcanization accelerator is a composition of MBTS and DTDM, and the mass ratio of the two is 3:2.

[0070] Comparative Example 1

[0071] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the composite modified rubber for automobile outer tires, in parts by mass, the raw materials are: 75 parts of natural rubber, 20.5 parts of composite rubber, 3.8 parts of aminosilane coupling agent, 32 parts of carbon material, 22.5 parts of modified nanoparticles, 9.8 parts of plasticizer, 3.4 parts of activator, 2.8 parts of dispersant, 1.2 parts of antioxidant, 2.1 parts of vulcanizing agent, and 1.6 parts of vulcanization accelerator.

[0072] Comparative Example 2

[0073] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the composite modified rubber for automobile outer tires, in parts by mass, the raw materials are: 61.6 parts of natural rubber, 34.5 parts of composite rubber, 3.8 parts of aminosilane coupling agent, 38.8 parts of carbon material, 10.5 parts of modified nanoparticles, 9.8 parts of plasticizer, 3.4 parts of activator, 1.1 parts of dispersant, 1.2 parts of antioxidant, 2.1 parts of vulcanizing agent, and 1.6 parts of vulcanization accelerator.

[0074] Comparative Example 3

[0075] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite rubber is a composition of styrene-butadiene rubber and liquid nitrile rubber, and the mass ratio of the two is 6:1.

[0076] The kinematic viscosity of the liquid nitrile rubber is 17500 cps, condition: 45°C, and it is purchased from NBR series products of corresponding viscosity sold by Shandong Shengrui Chemical Technology Co., Ltd.

[0077] Comparative Example 4

[0078] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite rubber is a composition of styrene-butadiene rubber and liquid nitrile rubber, and the mass ratio of the two is 1:1.

[0079] The kinematic viscosity of the liquid nitrile rubber is 8500 cps at 45° C., and the liquid nitrile rubber is purchased from NBR series products of corresponding viscosity sold by Shandong Shengrui Chemical Technology Co., Ltd.

[0080] Comparative Example 5

[0081] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles comprises the following specific steps: S1: 4 parts of titanium dioxide and 0.2 parts of ammonia water are mixed and added to 100 parts of deionized water, the temperature is raised to 65°C, and 60 parts of deionized water solution of 0.68 parts of ethyl orthosilicate, 0.1 parts of triethanolamine and 0.25 parts of γ-aminopropyltrimethoxysilane are added dropwise at a speed of 80 rpm, the addition time is 1 hour, and after the addition is completed, the temperature is kept for reaction for 1.2 hours, and after completion, the pre-treated particles are obtained by centrifugation, filtration and drying; S2: 1.2 parts of the pre-treated particles and 2.1 parts of anhydrous chlorine are mixed and added dropwise at a speed of 80 rpm. Aluminum hydroxide is mixed and added to 120 parts of DMF solution, the temperature is raised to 75°C and preheated for 2 hours, then the temperature is raised to 105°C and 40 parts of DMF solution containing 1.1 parts of 1,4-phthalic acid and 0.9 parts of 1,4-phthalic acid-NH2 are added dropwise at the same time, and the addition time is 2 hours; S3: after the addition is completed, the temperature is raised to 125°C, and the reflux reaction is kept for 18 hours. After the reaction is completed, it is naturally cooled to room temperature, and the solid product is collected by filtration, and washed with DMF several times to remove unreacted raw materials and other impurities. The filtered product is placed in a vacuum drying oven at 85°C and dried overnight to remove residual solvent, and the product is obtained after completion.

[0082] The average particle size of titanium dioxide is 30 nm; the average particle size of the obtained modified nanoparticles is 644 nm.

[0083] Comparative Example 6

[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles comprises the following specific steps: S1: 5.5 parts of titanium dioxide and 0.2 parts of ammonia water are mixed and added to 100 parts of deionized water, the temperature is raised to 65°C, and 60 parts of a deionized water solution of 0.15 parts of ethyl orthosilicate, 0.01 parts of triethanolamine and 0.05 parts of γ-aminopropyltrimethoxysilane are added dropwise at a speed of 80 rpm, the addition time is 1 hour, and after the addition is completed, the temperature is kept for reaction for 1.2 hours, and after the completion, the pretreated particles are centrifuged, filtered and dried to obtain pretreated particles; S2: 1.2 parts of pretreated particles and 2.1 parts of ammonia water are mixed and added dropwise at a speed of 80 rpm. Aluminum chloride water is mixed and added to 120 parts of DMF solution, the temperature is raised to 75°C and preheated for 2 hours, then the temperature is raised to 105°C and 40 parts of DMF solution containing 1.1 parts of 1,4-phthalic acid and 0.9 parts of 1,4-phthalic acid-NH2 are added dropwise at the same time, and the dropping time is 2 hours; S3: after the dropwise addition is completed, the temperature is raised to 125°C, and the reflux reaction is kept for 18 hours. After the reaction is completed, it is naturally cooled to room temperature, and the solid product is collected by filtration, and washed with DMF several times to remove unreacted raw materials and other impurities. The filtered product is placed in a vacuum drying oven at 85°C and dried overnight to remove residual solvent, and the product is obtained after completion.

[0085] The average particle size of the modified nanoparticles was 537 nm.

[0086] Comparative Example 7

[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles comprises the following specific steps: S1: 3.3 parts of titanium dioxide and 0.2 parts of ammonia water are mixed and added to 100 parts of deionized water, the temperature is raised to 65°C, and 60 parts of a deionized water solution of 0.45 parts of ethyl orthosilicate, 0.06 parts of triethanolamine and 0.11 parts of γ-aminopropyltrimethoxysilane are added dropwise at a speed of 80 rpm, the dropping time is 1 hour, and after the dropping is completed, the temperature is kept for reaction for 1.2 hours, and after the completion, the pretreated particles are centrifuged, filtered and dried to obtain pretreated particles; S2: 3.5 parts of pretreated particles and 1.5 parts of no Aluminum chloride water is mixed and added to 120 parts of DMF solution, the temperature is raised to 75°C and preheated for 2 hours, then the temperature is raised to 105°C and 40 parts of DMF solution containing 0.8 parts of 1,4-phthalic acid and 0.4 parts of 1,4-phthalic acid-NH2 are added dropwise respectively, and the dropping time is 2 hours; S3: after the dropwise addition is completed, the temperature is raised to 125°C, and the reflux reaction is kept for 18 hours. After the reaction is completed, it is naturally cooled to room temperature, and the solid product is collected by filtration, and washed with DMF several times to remove unreacted raw materials and other impurities. The filtered product is placed in a vacuum drying oven at 85°C and dried overnight to remove residual solvent, and the product is obtained after completion.

[0088] The average particle size of the modified nanoparticles was 533 nm.

[0089] Performance Evaluation

[0090] Wear resistance: The wear resistance of the composite modified rubber obtained in the embodiment and the comparative example was tested with reference to the standard GB / T 1689-2014. The load was 2.5 kg, the rotation speed was 70 r / min, the test speed was 1000 r, and the test value was the average value of 10 tests and recorded in Table 1.

[0091] Low temperature resistance test: The composite modified rubber obtained in the embodiment and the comparative example was tested for low temperature shrinkage resistance according to the standard GB / T 7758-2020. The starting temperature of the test was 23±2°C, the cooling rate was 1.5°C / min, and the values ​​at TR30 and TR50 were taken. The test value was the average value of 10 tests and recorded in Table 1.

[0092] Waterproof test: Take 2cm×2cm×0.5cm samples of the composite modified rubber prepared in the embodiment and the comparative example, and conduct a moisture permeability test. The test is conducted in accordance with the reference standard GB / T 1037-1988. The test temperature is 25±2°C, the test humidity is 50±5%RH, and the test value is the average value of 10 tests and recorded in Table 1.

[0093] Aging resistance test: Take 2cm×2cm×0.5cm samples of the composite modified rubber prepared in the embodiments and comparative examples, test their tensile strength (MPa), then store the samples in a constant temperature and humidity environment of 65±2℃, 80% relative humidity for 3 months, take them out after 3 months, test their tensile strength (MPa) again, calculate and record the tensile strength retention rate after the test (%, tensile strength retention rate %) = tensile strength after test / tensile strength before test × 100%, and take the average value of 10 samples tested and record it in Table 1.

[0094] Table 1 Performance test results

[0095]

[0096]

[0097] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of temperature resistance stability, waterproof performance, wear resistance and aging resistance. This is mainly due to the combined effect of the compounding scheme of the specific rubber material added as specified in the present application, the modified nanoparticles and other technical schemes. Comparative examples 1 to 7 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A composite modified rubber for automobile outer tires, characterized in that: Composite modified rubber for automobile outer tires, the raw materials are, by weight: 50-70 parts of natural rubber, 30-40 parts of composite rubber, 3-5 parts of aminosilane coupling agent, 30-50 parts of carbon material, 15-25 parts of modified nanoparticles, 8-14 parts of plasticizer, 3-5 parts of activator, 2-4 parts of dispersant, 1-1.5 parts of antioxidant, 1-3 parts of vulcanizing agent, 1-2 parts of vulcanization accelerator; The Mooney viscosity of the natural rubber is 85-100, condition: ML1+4@100°C; The composite rubber is a composition of styrene-butadiene rubber and liquid nitrile rubber; the mass ratio of the styrene-butadiene rubber to the liquid nitrile rubber is (3-4): (1.5-2); The kinematic viscosity of the liquid nitrile rubber is 11000-16000 cps, condition: 45°C; The Mooney viscosity of the styrene-butadiene rubber is 40-60, under the condition of ML1+4@100°C; The aminosilane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane; The carbon material is at least one of carbon black, carbon powder, graphene, graphene oxide and graphite; The plasticizer is at least one of aromatic oil, paraffin oil, naphthenic oil, white oil and silicone oil; The vulcanizing agent is sulfur; the vulcanization accelerator is a composition of MBTS and DTDM; the mass ratio of MBTS to DTDM is (3-3.5): (1.5-2).

2. The composite modified rubber for automobile outer tire according to claim 1, characterized in that: The mass ratio of the natural rubber, the composite rubber and the carbon material is (55-65):(32-38):(35-42).

3. The composite modified rubber for automobile outer tire according to claim 2, characterized in that: The mass ratio of the natural rubber, the modified nanoparticles and the dispersant is (55-65): (18-24): (2.5-3.5).

4. The composite modified rubber for automobile outer tire according to claim 3, characterized in that: The carbon material is carbon black; the average particle size of the carbon black is 30 to 50 nm.

5. The composite modified rubber for automobile outer tire according to claim 4, characterized in that: The preparation method of the modified nanoparticles comprises the following specific steps: S1: titanium dioxide and ammonia water are mixed and added to deionized water, the temperature is raised to 60-65° C., and a deionized water solution of ethyl orthosilicate, triethanolamine and γ-aminopropyltrimethoxysilane is added dropwise at a speed of 60-80 rpm, the addition time is 0.8-1 h, and after the addition is completed, the temperature is kept for reaction for 1.2-1.5 h, and after completion, the pretreated particles are obtained by centrifugation, filtration and drying; S2: Mix the pretreated particles and anhydrous aluminum chloride and add them to the DMF solution, heat it to 60-80°C and preheat it for 1-2h, then heat it to 100-110°C and simultaneously drop DMF solutions containing 1,4-benzenedicarboxylic acid and 1,4-benzenedicarboxylic acid-NH2, and the dropping time is 2-3h; S3: After the dropping is completed, heat it to 125-135°C, keep it warm and reflux it for 16-18h, and naturally cool it to room temperature after the reaction is completed. Collect the solid product by filtration, and wash it with DMF several times to remove unreacted raw materials and other impurities. Dry the filtered product in a vacuum drying oven at 80-90°C overnight to remove residual solvent, and it is obtained after completion.

6. The composite modified rubber for automobile outer tire according to claim 5, characterized in that: The mass ratio of titanium dioxide, tetraethyl orthosilicate, triethanolamine and gamma-aminopropyltrimethoxysilane is (3-3.5): (0.3-0.5): (0.05-0.08): (0.1-0.12).

7. The composite modified rubber for automobile outer tire according to claim 6, characterized in that: The mass ratio of the pretreated particles, anhydrous aluminum chloride, 1,4-phthalic acid and 1,4-phthalic acid-NH2 is (1-1.5): (2-2.2): (1-1.2): (0.8-1).

8. The composite modified rubber for automobile outer tire according to claim 7, characterized in that: The average particle size of the titanium dioxide is 10-20 nm; the average particle size of the modified nanoparticles is 400-480 nm.

9. The composite modified rubber for automobile outer tire according to claim 7, characterized in that: The dispersant is at least one of zinc stearate, calcium stearate, tributyl phosphate, triphenyl phosphate and lauryl alcohol polyoxyethylene ether.

10. A method for preparing a composite modified rubber for automobile outer tire according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Put natural rubber and composite rubber into an internal mixer, preheat at 90-95℃ for 10-15min, then add aminosilane coupling agent, carbon material, modified nanoparticles and dispersant and mix for 6-8min, continue to add plasticizer, activator and antioxidant and mix for 8-10min; S2: Add vulcanizer and vulcanization accelerator and mix for 5-7min, ensure that all ingredients are evenly dispersed, then take out the mixed rubber, cool to room temperature, and extrude the cooled rubber into shape using an extruder; S3: Put the molded rubber into a vulcanizing tank, set the vulcanization temperature to 130-145℃, the vulcanization pressure to 1.2-1.6MPa, and the vulcanization time to 30-35min. After the vulcanization is completed, take out the rubber and cool it naturally to room temperature.

Citation Information

Patent Citations

  • Tread rubber composite material containing modified graphene oxide compound and preparation method of tread rubber composite material containing modified graphene oxide compound

    CN105801943A

  • Preparation method of micron-sized porous hollow silicon spheres

    CN111232985A

  • Preparation of water-soluble metal-organic framework composite material and application of water-soluble metal-organic framework composite material in detecting concentration of fluorine ions in water

    CN111454461A

  • Modified PET base material for solar cell backboard and preparation method of modified PET base material

    CN112745645A

  • Light-colored conductive adhesive as well as preparation method and application thereof

    CN114774052A